KEANEKARAGAMAN JENIS GANODERMA KAWASAN TAMAN NASIONAL GUNUNG RINJANI (TNGR) NUSA TENGGARA BARAT - Dharmawibawa, Iwan Doddy; Imran, Ali; Ulan, Milatul (Bioscientist : Jurnal Ilmiah Biologi, 2015)
Ganoderma is one of the fungi that can function as a medicine, besides it can function as a decomposer to accelerate the material cycle in the forest ecosystem. This study aims to determine the spread of types of Ganoderma especially along the Sebau road in the Gunung Rinjani National Park area. This study used a descriptive explorative line transect and was carried out in May 2015. The identification of Ganoderma samples was carried out by matching the macroscopic Ganoderma profile with an identification book and available literature. Makrofungi found 14 species, 5 of which included the Ganodermataceae family, namely Ganoderma sp., Ganoderma adspersum, Ganoderma applanatum, Ganoderma lucidium, and Ganoderma tsugae while 9 species including the Polyporaceae family included Polyporus sp., Polyporus versicolor, Trametes elegan, Trametes versicolor, Trametes sp., Trametes sp.2, Datronia sp., Pycnoporus cinnabarinus, and Microporus sp.